Reviewing the intellectual structure of product modularization: Toward a common view and future research agenda - Kai G. Mertens; Christoph Rennpferdt; Erik Greve; Dieter Krause; Matthias Meyer (Journal of Product Innovation Management, 2022)
Product modularization in new product development has attracted considerable interest among scholars and practitioners from diverse fields of specialization. This has resulted in cross-disciplinary diversity in the field, diverting attention from its overall intellectual structure and hindering the development of a common view and shared concepts. Extant research lacks an integrative review, transcending a focal discipline that could identify gaps and ambiguities while making recommendations to advance the field. Considering a period of 300.167emyears (1990–2020), we generate a data set of 2988 citing publications to which we apply a co-citation analysis. Thereby, we uncover the intellectual structure of the field and find three research perspectives that represent key knowledge bases: (1) product system, (2) production system, and (3) organizational system. Delimiting the data set into four periods, we can track developments over time, where we notice an increasing disintegration of the product system perspective, which is rooted in the discipline of engineering design. Within the two other perspectives, we document extensive dynamism in terms of publications, especially in the two most recent periods, indicating an active discussion and a potential receptivity to new trends. For these periods, we also identify an emerging cluster of fundamental publications and an increasing emphasis on the concept of system architecture. Leveraging the synthesis of these results, we forge links between neighboring disciplines and recommend avenues for further research, ideally to develop a more common view.
Keywords: 650; innovation; modularity; modularization; new product development; platform; review